Premeditating Stance: Countdown to the Liberian Civil War - Talibu, Oladimeji; Abdulrasheed, Adamu (Kashere Journal of Politics and International Relations, 2025)
War in the international system is fast becoming a recurrent geo-political concern to state and non-state actors. The motivations for continuous increment of war and conflict need to be explored to provide sustainable mechanism for preventing the repeated occurrence. One of such wars occurred in Liberia and persisted for a decade. Assessing the premeditating stage of the war and issues that fuelled it is a focus of this paper. Thus, the current research assesses the role of historical narratives in the Liberian civil war as well as the primordial sentiments that developed among the populace. The assessment of issues and factors that eventually sparked civil war in Liberia may serve as an important guidepost to global, regional, and sub-regional multilateral institutions in preventing the same scenario reoccurring in other parts of the world. In this manner, the research has found that tribal and ethnic sentiments played a pivotal role in the Liberia civil war. Again, injustice, inequality and lack of resilient institutions are found to be absent in Liberia before and after the civil war. The research thus recommends that for such civil war to be prevented from happening in other parts of the world, the concerned global actors like Governmental and Non-Governmental international institutions should promote the need for democratic governance that embodies equitable distribution of resources, resilient institutions, and promotion of national integration agenda. The research adopted qualitative latent content analysis as a methodological approach.